Postural control and posture-unrelated attention control in advanced age—An exploratory study. (October 2018) - Netz, Yael; Zeev, Aviva; Dunsky, Ayelet
Highlights: Women, especially the young-old group, have better static balance than men. Men have better dynamicbalance than women. Posture-unrelated attention control is related to static balance in women. Posture-unrelated attention control is related to dynamic balance in men. Postural control is explained by "basic" inhibition and by auditory-distraction tasks. Abstract: Objectives: The link between postural control and cognition is under-studied, especially in healthy older adults. In the present study, we examined the link between postural control and posture-unrelated attention control. Study design and outcome measures: Healthy individuals (n = 112) – men aged 77.2 ± 5.5, and two groups of women, aged 78.6 ± 3.5 and 68.9 ± 3.7 – participated in this cross-sectional study. Postural control was assessed by static balance (SB) posturography in eight standing positions, and by two measures of dynamic balance (DB): the Timed Up-and-Go (TUG) test, and the Functional Reach Test (FRT). Attention control (inhibition) was assessed by the Continuous Performance Test (CPT) measuring Go/NoGo tasks with and without visual and audio distractors. Results: Men tended to perform better on DB and women on SB. In the men, significant correlations were observed between Go/NoGo tasks and DB (r range: 0.373 to 0.653 for TUG, and -0.342 to -0.530 for FRT). In the younger women, Go/NoGo tasks were correlated with SB (r range: 0.323 to 0.572), and no correlations were observed in the older women. Go/NoGo tasks without distractions followed by tasks with audio distractors explained postural control measures. Conclusions: Posture-unrelated attention inhibition was associated with SB in the women and with DB in the men. Tasks with no distractions explained the variability in postural control in both genders. It is recommended to examine the effect of balance exercises on postural control and posture-unrelated attention control in both genders, and the contribution of the relationship between postural control and posture-unrelated attention control to falls in old age.